ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PROGRAM LINEAR DITINJAU DARI ADVERSITY QUOTIENT - Finlantya Elsa Hutami; Dinawati Trapsilasiwi; Randi Pratama Murtikusuma (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
This research aims to analyze student’s error types in solving linear programming problems based on Newman’s error analysis viewed from Adversity Quotient (AQ). This research approach is qualitative descriptive. Subjects in this research are 6 students in class X TKR 3 of SMKN 2 Jember. There are 2 climber students, 2 camper students, and 2 quitter students. Instruments that were used in this research to collect the data are ARP questionnaire, linear programming problem, interview guide, and validation sheets. Based on the result of this research, the climber students are able to do comprehension error, process skill error, and encoding error. The camper students are able to do comprehension error, transformation error, process skill error, and encoding error. The quitter students are able to do reading error, comprehension error, transformation error, process skill error, and encoding error.